Narrative review. Complications in the mother, fetus, and neonate due to cocaine use during pregnancy - Londoño Restrepo, Johanna; Aristizábal Echeverry, Liseht Carolina (Medicina UPB, 2016)
Latin America reported the following data regarding substance abuse in pregnant women: 44% alcohol, 51.8% tobacco, 8.3% amphetamines, 2.5% cocaine and 2% cannabis. Pregnant women using these substances are a risk factor for health institutions due to the physical, psychological, social, and family consequences for the mother and the newborn infant. Thus, intersectoral and interdisciplinary interventions are necessary to treat this problem. This review describes the physical and behavioral complications in the mother, fetus, and neonate as a result of the use of cocaine and its derivatives during pregnancy. A narrative review was performed by means of a search of journals indexed in PubMed, Lilacs, Ovid, Science Direct from 2000 to 2015. Keywords were used in order to perform a standardized literature search, and data from research articles, systematic reviews, meta-analyses were included. Pregnant consumers of cocaine involve a risk factor for public health due to the physical, psychological, family, and social consequences for the mother, the newborn, and infant, such as high blood pressure, abruption, intrauterine growth retardation, and neonatal abstinence syndrome. It is necessary for local health departments to develop, adopt, and adapt reporting, management, and monitoring protocols for consuming mothers and their children in order to promote healthy habits, prevention of obstetrics and neonatal complications and to monitor the impact on growth and development in children.